Internalization Of Pancasila Values Based On School Culture - Bella Dwi Septiani; Moh. Wahyu Kurniawan (JED (Jurnal Etika Demokrasi), 2022)
Strengthening Pancasila values in schools can be carried out in a structured manner through school programs in order to become a habituation for the application of character values carried out by students in school cultural activities. Students who have the character of Pancasila values are the main basis for welcoming the golden generation in 2045. This research aims to analyze the Internalization of Pancasila Values Based on School Culture as well as analyze the impact of internalization of Pancasila values based on school culture in everyday life. This research method uses qualitative descriptive, while the data collection techniques in this study are observation, interview, FGD, and documentation. The data analysis techniques used are Miles and Huberman which include data collection, data reduction, presenting data, and drawing conclusions. Furthermore, the data is tested for validity with credibility, transferability, dependability, and confirmability. The results of this study include learning process activities that are integrated in all subjects. Internalization of the value of Pancasila as a form of local wisdom in cultural-based national insights has the character of nationalism, integrity and mutual cooperation, and has knowledge related to national insights and love of the homeland (WANGSACITA) judging from the supporting factors for the internalization of Pancasila values that are used as a school culture, so that students have a spirit of unity and unity in behaving in the midst of student diversity in school.